Improved therapeutic potential of MSCs by genetic modification. Issue 8 (December 2018) - Wei, Wei; Huang, Yong; Li, Dan; Gou, Hong-Feng; Wang, Wei
Abstract Mesenchymal stem cells (MSCs), well-studied adult stem cells in various tissues, possess multi-lineage differentiation potential and anti-inflammatory properties. MSCs have been approved to regenerate lineage-specific cells to replace injured cells in tissues. MSCs are approved to treat inflammatory diseases. With the discovery of genes important for the repair of damaged tissues, MSCs genetically modified by such genes hold improved therapeutic potential. In this review, we summarised the uses of genetically modified MSCs to treat different diseases, including bone diseases, cardiovascular diseases, autoimmune diseases, central nervous system disorders, and cancer. To better understand the exact role of genetically modified MSCs, key mechanisms determining, which genes are selected to be used for modifying MSCs and improvements in post-genetic modification are discussed. Therapeutic benefits enhanced by genetic modifications are to be documented by further clinical studies.